Burn Wound Healing Activity of Ethanolic Extract of Acalypha indica in Oinment Formulated against Rabbits (Ocyctagus caniculus) - Fitri, Khairani; Khairani, Tetty Noverita; Sinaga, Fajar Apollo; Talunohi, Amenia Gracia (Asian Journal of Pharmaceutical Research and Development, 2020)
Objectives: The purpose of this study was to determine burn wound healing activity of Acalypha indica L. in oinment formulated. Design: This study uses an experimental laboratory design. This study used rabbits as test animals induced by burns with hot iron plates on the back. Extract ointment applied to the wound then observed the development of healing. Interventions: The extract was formulated in ointments with concentrations of 3, 5 and 7%. positive control used was ointment containing sesame oil and negative control used is an ointment base. Main outcome measure: The results showed a concentration of 3% had a slow and low effect, at a concentration of 5% it had a moderate healing phase, and a concentration of 7% had a good healing phase. Conclusion: The ointments containing Acalypha indica leaf extracts have good activity in healing burns in rabbits.